INGLIS HÁM QARAQALPAQ TILLERINDEGI ASTRAL MIFOLOGIYALÍQ BIRLIKLERDIŃ SEMANTIKALÍQ ÓZGEShELIKLERI - Usenova, V.J. (SCIENCE and SOCIETY, 2026)
This article examines the semantic features of astral mythological units based on definitional analysis within the framework of cognitive linguistics and linguocultural studies.